PENINGKATAN MOTIVASI BELAJAR IPAS MELALUI MODEL PEMBELAJARAN QUANTUM TEACHING PADA SISWA KELAS V SDN 008 LANGGINI - Nurul Hidayah; Afriza Rahma Rani; Putri Hana Pebriana; Mufarizuddin; Joni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low motivation of students in the material of my dear earth, my poor earth in class V of SDN 008 Langgini. One solution to overcome this problem is to apply the Quantum Teaching learning model. The purpose of this study is to describe the increase in student learning motivation in the material of my dear earth, my poor earth by applying the Quantum Teaching learning model of class V students of SDN 008 Langgini. The research method is classroom action research (CAR) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation and reflection. The subjects of this study were 15 class V students. Data collection techniques were documentation, observation, questionnaires and tests. Based on the results of data analysis, it can be seen that there is an increase in student motivation results after the action, on average in the pre-action activities, the average class value is 55.06 with a classical completeness of 40%, increasing in cycle 1 meeting 1 to 56.6 with a classical completeness of 46%, increasing in cycle 1 meeting 2 to 60.8 with a classical completeness of 53%. The average class value in cycle 2 meeting 1 is 70.73 with a classical completeness of 66%., and increasing in cycle 2 meeting 2, namely 76.33 with a classical completeness of 80%. So it can be concluded that the application of the Quantum Teaching learning model can increase the learning motivation of class V students of SDN 008 Langgini